Confraternity Documents Issued for the Olomouc Convent of Canons Regular of St. Augustine in the First Quarter of the 16th Century / Konfraternitní listiny vydané pro olomoucký konvent řeholních kanovníků sv. Augustina v první čtvrtině 16. století - KRAFL, Otmar (Studia Historica Nitriensia)
The monasteries of Canons Regular of St. Augustine were bound by confraternities. Monastic convents issued charters, which contained obligations to celebrate church services and prayers for deceased members of the other convent. The aim of the article is to publish an edition of three confraternity documents issued for the Olomouc convent of Canons Regular in the first quarter of the 16th century. They survived in the archive of the Olomouc convent of Canons Regular and are currently deposited in the Moravian Archives in Brno. They were issued by Nicolas provost and convent in Šternberk in 1503; by Andrew provost and convent in Borovany in 1505; and, finally, by Benedict provost and convent in Šternberk in 1522.